2021
DOI: 10.1096/fj.202100154r
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity between β‐agonists and c‐Abl inhibitors in regulating airway smooth muscle relaxation

Abstract: Current therapeutic approaches to avoid or reverse bronchoconstriction rely primarily on β2 adrenoceptor agonists (β‐agonists) that regulate pharmacomechanical coupling/cross bridge cycling in airway smooth muscle (ASM). Targeting actin cytoskeleton polymerization in ASM represents an alternative means to regulate ASM contraction. Herein we report the cooperative effects of targeting these distinct pathways with β‐agonists and inhibitors of the mammalian Abelson tyrosine kinase (Abl1 or c‐Abl). The cooperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…The role of nestin in smooth muscle contraction has not been previously investigated. We have established the technique to determine airway narrowing of PCLS [ 38 , 52 ]. We treated human PCLS with control or nestin siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…The role of nestin in smooth muscle contraction has not been previously investigated. We have established the technique to determine airway narrowing of PCLS [ 38 , 52 ]. We treated human PCLS with control or nestin siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are supported by the facts that (1) actin polymerisation is of impact for the contractile effect of PDGF-BB in pulmonary veins (GP) [ 19 ] and (2) that actin polymerisation is of relevance for airway hyperresponsiveness [ 62 , 65 ]. Further, Nayak et al [ 66 ] recently demonstrated the additive effects of beta-agonists and Abl-inhibitors on the airway tone in murine PCLS and in mice with the flexiVent system [ 66 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Our results are supported by those of Chopra et al [ 50 ] who proved a relaxant effect of the TKIs ST638, genistein and tyrphostin A47 in isolated bronchioles of rats. Recently, Nayak et al [ 66 ] showed in murine PCLS and in a murine in vivo model (flexiVent) that TKIs and β-agonist act synergistic within the context of bronchorelaxation. Beyond, the relaxant effects of several TKIs, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The day after, slices are washed and returned to the incubator for 1 h before experiments (Koziol‐White, 2022; Sanderson, 2011; Slack et al, 2013). The preparation of PCLS via inflation of warm agarose requires specific buffers such as the Hanks' balanced salt solution (HBSS) with Ca 2+ and Mg 2+ supplemented with HEPES and Dulbecco's modified Eagle medium (DMEM)/F‐12 with antibiotics (Bai et al, 2016; Nayak et al, 2021).…”
Section: Tissue Collection Preparation and Equipmentmentioning
confidence: 99%